Socio-technical imaginaries and the future of teaching: how discourses of digital transformation reconstitute social practices from the present - Estormovski, Renata Cecilia (Revista Española de Educación Comparada, 2025)
This study aims to analyze the discourses of teacher digital transformation disseminated by reference documents in the educational field, discussing the socio-technical imaginaries they promote in relation to the technosolutionist perspectives of the Brazilian educational context. An exploratory study based on Norman Fairclough’s Critical Discourse Analysis method examines four documents by different authors, namely The End of School as You Know It: Education in 2050, by European EdTech GoStudent; Working and learning together, by the Organization for Economic Cooperation and Development (OECD); the Estratégia Brasileira de Inteligência Artificial, by the Ministério da Ciência, Tecnologia e Inovações do Governo Brasileiro; and the Recomendações para implementação da BNCC Computação, by the Fundação Telefônica Vivo. Semantic fields emerge from these materials, such as technological solutionism, in which teachers take on the role of coaches, while non-teachers provide specialized knowledge to students together with technology; at the same time, it guides the formation of digital skills in teachers in the present, making them a tool for accessing digital resources, in the present to make this future possible. Teaching, in an idealized future amidst the dynamics of digital privatization, is presented as separate from pedagogical decisions (to be made by algorithms), and restricted to motivating students’ socio-emotional skills; at the same time, however, concerns are identified about the development of basic digital skills by teachers today, especially in the Brazilian scenario. The study corroborates the perception that discourses, more than texts, are ways of structuring social practices, which constitute conventions and norms, with the references analyzed manifesting socio-technical imaginaries, constituted in digital governance networks, which project a re-signification of teaching in a context in which education is situated as inseparable from digitalization. Keywords: Education policies; Digital governance of education; Educational technosolutionism; The teaching profession